PERAN PEREMPUAN DALAM MERUMAH - Koniherawati; Priyo Pratikno (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) Universitas Kristen Duta Wacana Yogyakarta, 2015)
Title: The Roles of Wemen in Domestic Activities Women, especially mother, has a major role in build and maintain a home, as shown by various ethnic groups in the world. The various roles of woman indicated in protection, give a sense of comfort, and safety for the baby and all family member. Mother is person who gives a shade of home through food processing activities and how to primp her self. The efforts collecting building materials, to decorate, and chose home furnishings are dominant activities that mother does. This study is explore the problems of designing of home by women in the past were intended to justify the design of art and architecture. This study based on literature that shows the role of the mother in build, manage, and interpreting a house. The method of this study base on secondary data and then weave every aspects to build the hypotheses. These information show that women as housewives have a significant role in shaping the house as culturally or physically. The results showed that women as mother very dominant in giving the feel and shape of house.